A mediação na adoção de crianças indígenas no Estado do Amazonas: uma proposta descolonial para um problema real - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The Brazilian Child and Youth Statute explicitly recognizes the children of diverse ethnic origin, as indigenous and quilombolas, ainda assure them the respect of their social and cultural identity, their habits and traditions, also their institutions, as long as they are not incompatible with the fundamental rights established at the Statute or the Federal Constitution. The general aim of the research consists in analyzing the proposal of intercultural mediation as an effective alternative to assure the interests and rights of indigenous children at the judicial process of adoption. It has as its first specific objective write about the current protection of children and youth sistem at the Brazilian legal order, specially about the best interest of youth at indigenous adoption. As second aim, it tries to determine the importance of the restructuring of the justice system from the new latin american constitutionalism to propose solutions to the conflicts emerged in the adoption judicial process involving indienous community. As a third specific objective, the research tries to demonstrate that the institution of intercultural mediation can be applied to the amazonic reality as a way to guarantee the participation of all parts involved at the judicial process and the definition of the best interest of children or youth indigenous. Therefore, using the gathering of primary data from scientific articles concerned to the descoloniality theme and related bibliography, it tries to include the intercultural bias at mediation in indigenous adoption.
Mediation in the adoption of indigenous children in the state of Amazonas: a decolonial proposal for a real problem
Keywords: CIENCIAS SOCIAIS APLICADAS: DIREITO: DIREITO PUBLICO: DIREITO CONSTITUCIONAL; Mediação; Criança; Indígena; Adoção; Descolonial